Meaning, function and overcoming of the guilt in university young people: An analysis by sex - Valdez Medina , José Luis (Consorcio de Universidades Mexicanas A.C., 2013)
The objective of this research was to study the definition, demonstrations and overcoming guilt in college students through exploratory qualitative assessment. An instrument was constructed consisting of 11 questions on the theme of guilt, which was applied to 300 university students, divided equally by gender, aged between 18 and 25. The application was made as an individual interview lasting approximately 30 minutes per participant. The results were processed using content analysis technique (Alvarez-Gayou, 2005), which allows to make findings identifying systematic and objective characteristics of the answers given. Research shows that men and women conceive guilt as the feeling that comes after doing something wrong or is believed to be improper according to the value judgments, which causes remorse and repentance. The strategies that men and women used to overcome this feeling are the reflection and repair damage done to the other. However, men also said that they evade or justify the situation, while women seek resolution directly. Guilt is a psycho-social-cultural strategy that serves as a mechanism of social control, its purpose is to effectively regulate the social behavior of the individual, the same that leads to apologize, implying an attempt to regain the trust itself and with the other people, in order to reduce the threat and live without fear.